I/O performance challenges at leadership scale - Lang, Samuel; Carns, Philip; Latham, Robert; Ross, Robert; Harms, Kevin; Allcock, William (Proceedings of the Conference on High Performance Computing Networking, Storage and Analysis, 2009)
Today's top high performance computing systems run applications with hundreds of thousands of processes, contain hundreds of storage nodes, and must meet massive I/O requirements for capacity and performance. These leadership-class systems face daunting challenges to deploying scalable I/O systems. In this paper we present a case study of the I/O challenges to performance and scalability on Intrepid, the IBM Blue Gene/P system at the Argonne Leadership Computing Facility. Listed in the top 5 fastest supercomputers of 2008, Intrepid runs computational science applications with intensive demands on the I/O system. We show that Intrepid's file and storage system sustain high performance under varying workloads as the applications scale with the number of processes.